Cytotoxicity of Acanthus ilicifolius root endophytes based on acid-induced enhancement and metabolites of Penicillium javanicum - ERNY QUROTUL AINY; KHOLIS A. AUDAH; MARSELINA I. TAN; I NYOMAN P. ARYANTHA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Ainy EQ, Audah KA, Tan MI, Aryantha INP. 2026. Cytotoxicity of Acanthus ilicifolius root endophytes based on acid-induced enhancement and metabolites of Penicillium javanicum. Biodiversitas 27 (3): d270322. https://doi.org/10.13057/biodiv/d270322. Mangrove ecosystems are characterized by extreme environmental fluctuations, driving associated endophytic fungi to evolve adaptive metabolic strategies. These microbial communities represent an untapped reservoir of chemical diversity, yet their metabolic response to abiotic stressors, such as acidity, remains underexplored. This study investigates the ecological and chemical plasticity of endophytic fungi isolated from Acanthus ilicifolius roots. Using a stress-driven culture approach, we evaluated the effect of acidic fermentation on the metabolic profiles and cytotoxic potential of bioactive isolates. Among the screened strains, Penicillium javanicum 2RA6 exhibited a distinct physiological response to acidic stress. While neutral conditions favored vegetative growth, acidic fermentation triggered a fundamental metabolic reprogramming, shifting the biosynthetic output from constitutive polyketides to a specialized stress ‘portfolio’. Comparative metabolomics revealed the enrichment of diverse fatty acid amides (including putative 9-oxo-(10E, 12E)-Octadecadienoic Acid (9-oxo-ODA), α-Eleostearic Acid (α-EA), and Palmitoyl Ethanolamide (PEA)) and diketopiperazines. This chemical reorganization correlated with a marked increase in specific cytotoxicity against MCF-7 breast cancer cells, mediated primarily through apoptosis-like pathways. These findings suggest that mimicking environmental stressors is a viable strategy to unlock cryptic biosynthetic gene clusters. This study highlights the importance of mangrove habitats as reservoirs of metabolic diversity and demonstrates that acid-enhanced cultivation can access bioactive fungal metabolites typically overlooked in standard fermentations.